2021
DOI: 10.1002/14651858.cd012768.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Xpert MTB/RIF Ultra and Xpert MTB/RIF assays for extrapulmonary tuberculosis and rifampicin resistance in adults

Abstract: Background Xpert MTB/RIF Ultra (Xpert Ultra) and Xpert MTB/RIF are World Health Organization (WHO)-recommended rapid nucleic acid amplification tests (NAATs) widely used for simultaneous detection of Mycobacterium tuberculosis complex and rifampicin resistance in sputum. To extend our previous review on extrapulmonary tuberculosis (Kohli 2018), we performed this update to inform updated WHO policy (WHO Consolidated Guidelines (Module 3) 2020). Objectives To estimate diagnostic accuracy of Xpert Ultra and Xpert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 324 publications
(34 reference statements)
2
83
0
4
Order By: Relevance
“…Due to the low sensitivity and specificity of AFB microscopy when compared with culture method ( Karadaǧ et al, 2013 ; Molicotti et al, 2014 ; Pk et al, 2017 ; Bahr et al, 2018 ), molecular methods (as Xpert ® MTB/RIF assay) were introduced to improve the speed and specificity of TB diagnosis mainly in the context of extrapulmonary and FFPE samples, when bacterial load is low, and culture is not even possible. Sensitivities of Xpert ® MTB/RIF and its ultra version reported in fresh non-FFPE clinical samples, so far, are always higher than 60% ( Tortoli et al, 2012 ; Sauzullo et al, 2016 ; Lee et al, 2017 ; Bahr et al, 2018 ; Dorman et al, 2018 ; Sarfaraz et al, 2018 ; Sulis et al, 2018 ; Aydemir et al, 2019 ; Kohli et al, 2021 ) and can reach more than 90% only in some body districts ( Mazzola et al, 2016 ). The few data available regarding the Xpert assay performances in FFPE samples are based on a few clinical biopsies and reported a wide range of sensitivities, which were not even concordant (from 97.6% in the case of the Ultra version to 53.2% in the case of the first MTB/RIF assay) ( Seo et al, 2014 ; Du et al, 2019 ; Njau et al, 2019 ; Budvytiene and Banaei, 2020 ; Huang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the low sensitivity and specificity of AFB microscopy when compared with culture method ( Karadaǧ et al, 2013 ; Molicotti et al, 2014 ; Pk et al, 2017 ; Bahr et al, 2018 ), molecular methods (as Xpert ® MTB/RIF assay) were introduced to improve the speed and specificity of TB diagnosis mainly in the context of extrapulmonary and FFPE samples, when bacterial load is low, and culture is not even possible. Sensitivities of Xpert ® MTB/RIF and its ultra version reported in fresh non-FFPE clinical samples, so far, are always higher than 60% ( Tortoli et al, 2012 ; Sauzullo et al, 2016 ; Lee et al, 2017 ; Bahr et al, 2018 ; Dorman et al, 2018 ; Sarfaraz et al, 2018 ; Sulis et al, 2018 ; Aydemir et al, 2019 ; Kohli et al, 2021 ) and can reach more than 90% only in some body districts ( Mazzola et al, 2016 ). The few data available regarding the Xpert assay performances in FFPE samples are based on a few clinical biopsies and reported a wide range of sensitivities, which were not even concordant (from 97.6% in the case of the Ultra version to 53.2% in the case of the first MTB/RIF assay) ( Seo et al, 2014 ; Du et al, 2019 ; Njau et al, 2019 ; Budvytiene and Banaei, 2020 ; Huang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most of the extrapulmonary specimens were oligosaccharides at the initial stage of the disease, making the diagnosis of various tests less sensitive. For example, MTB culture reduces sensitivity to paucibacillary infection and take several weeks to produce results (19). We also found that, unlike RR/MDR-PTB, RR/MDR-EPTB relies more on Xpert to establish the diagnosis.…”
Section: Discussionmentioning
confidence: 72%
“…However, specificity is reduced by 2.7% (95.6% vs. 98.4%). 8 The WHO technical expert group concludes that Ultra has a higher sensitivity than Xpert MTB/RIF particularly in smear-negative culture-positive specimens, extrapulmonary specimens, and testing specimens from HIV-infected patients and children. Among people without HIV infection, for sputum specimens, an initial “trace call” positive result should be confirmed by testing a fresh specimen with clinical and radiological correlation.…”
Section: B Acterial I Nfectionsmentioning
confidence: 99%